2021
DOI: 10.1128/mbio.03589-20
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Signaling Is a Common Factor Driving Streptococcus pneumoniae and Influenza A Virus Shedding and Transmission

Abstract: The dynamics underlying respiratory contagion (the transmission of infectious agents from the airways) are poorly understood. We investigated host factors involved in the transmission of the leading respiratory pathogen Streptococcus pneumoniae. Using an infant mouse model, we examined whether S. pneumoniae triggers inflammatory pathways shared by influenza A virus (IAV) to promote nasal secretions and shedding from the upper respiratory tract to facilitate transit to new hosts. Here, we show that amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…However, during the period of stable colonization (>24hrs p.i. ), when Spn has migrated to the glycocalyx, we confirmed that the presence of Spn increases URT secretions, a result that recapitulates the correlation between rhinitis symptoms and Spn carriage in young children [40,41]. Adults, who have a lower density of colonizing Spn, have less pronounced secretions during episodes of carriage.…”
Section: Plos Pathogenssupporting
confidence: 79%
See 1 more Smart Citation
“…However, during the period of stable colonization (>24hrs p.i. ), when Spn has migrated to the glycocalyx, we confirmed that the presence of Spn increases URT secretions, a result that recapitulates the correlation between rhinitis symptoms and Spn carriage in young children [40,41]. Adults, who have a lower density of colonizing Spn, have less pronounced secretions during episodes of carriage.…”
Section: Plos Pathogenssupporting
confidence: 79%
“…Since neuraminidases mediate both an effect on mucus production and evasion it is difficult to test conditions that could distinguish these effects. Interestingly, influenza virus, which contains a neuraminidase, induces copious mucus production in the URT [5,40]. In the setting of influenza A co-infection, the neuraminidase-deficient Spn mutant has been shown to exhibit decreased levels of colonization compared to controls without influenza A co-infection [5,42].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…It has been shown that Spn stimulates IFN-I production and upregulates the expression of IFN-stimulated genes in both mouse and human studies ( 17 , 29 ). Therefore, it is possible that pneumococcal colonization interferes with the replication cycle of the virus ( 30 , 31 ) and contributes to host antiviral defenses by governing the production of IFNs ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports demonstrated that SARS-CoV-2 virus is effective at avoiding or delaying the triggering of early innate immune responses, such as type I interferons (IFNs) in vitro 29 and in humans 30,31 . On the other hand, it has been shown that S. pneumoniae infection stimulates IFN-I production and upregulates the expression of IFN-stimulated genes in both mice and human studies 16,32 . Therefore, it is possible that pneumococcal colonisation interferes with the replication cycle of the virus 33,34 and contributes to host antiviral defences by governing the production of IFNs 35,36 .…”
Section: Discussionmentioning
confidence: 99%